ANALISIS PENATALAKSANAAN PROGRAM PENANGGULANGAN TUBERKULOSIS PARU DENGAN STRATEGI DOTS DI PUSKESMAS DESA LALANG KECAMATAN MEDAN SUNGGAL TAHUN 2015 - muhammad mansur (Lingkungan dan Kesehatan Kerja, 2015)
ABSTRACT Pulmonary tuberculosis disease is a contagious infection affect widely to the quality of life and threaten the safety of human soul. Since 1995, Indonesia implement a program of pulmonary tuberculosis eradiction through pulmonary tuberculosis treatment with DOTS strategy (Directly Observed Treatment Shortcourse) which can break the chain of transmisssion of the illness. Number of patients in Desa Lalang Puskesmas with pulmonary tuberculosis BTA positive in 2014 as many as 42 people with 59,52% cure rate. This means that the cure rate at Desa Lalang Puskesmas has not reached the target is at least 85%. This research was a qualitative research that aimed to see more clearly and deeply about the management of pulmonary tuberculosis program with DOTS strategy at Desa Lalang Puskesmas. Methods of data collection was done by in-depth interviews and observation. Informants in this research amounted to 7 peoples, consisting of employee for Health Problems Tackling at Health Department city of Medan, Head of Desa Lalang Puskesmas, pulmonary tuberculosis officer in Desa Lalang Puskesmas, 2  patients with TB, 2 people of PMO. Analysis of data used Miles and Huberman. The results showed that the management of pulmonary tuberculosis program with DOTS strategy at Desa Lalang Puskesmas not running optimally. It is seen from the quality of personnel is still lacking in the pulmonary tuberculosis case finding effort and training to accommodate patients with TB in sputum, pulmonary tuberculosis case finding carried passively by waiting patients came with medical treatment, lack of knowledge of the patients in the sputum accommodate the correct diagnosis so that an error occurred when sputum examined microscopically by officer. Based on the results of the research, expected to Medan City Health Department in order to constantly monitor and evaluate the implementation of programs specifically pulmonary tuberculosis and sustainable and provides for the allocation of funds to the officers of TB in public health center in an effort to crawl, case finding and counseling. Officers pulmonary tuberculosis in order to perform the invention of active pulmonary tuberculosis cases to homes and provide counseling to patients about pulmonary tuberculosis disease and its treatment.